Testing the Robustness of Local Network Metrics in Research on Archeological Local Transport Networks - Groenhuijzen, Mark R.; Verhagen, Philip (Frontiers in Digital Humanities, 2016)
With the increased application of network analysis in archaeology to form hypotheses, particularly concerning the research on mobility, a need has arisen to validate the network analysis results. This paper presents a case study of a local transport network in the Dutch part of the Roman limes between 70-270 AD created using a least-cost approach, and tests the robustness of the local network metric of betweenness centrality and the archaeological interpretation thereof. It is demonstrated that while the majority of sites have a robust and thus reliable betweenness centrality, there are still a large number of sites for which the network measurements are very dependent on the precise structure of the network present. Testing robustness of network analysis results thus proves a useful tool both for validating the network modeling results as well as the archaeological interpretations of that network.